Reconceptualizing Traditional Ablution Instruction: CTL and TPACK Integration in Fiqh Curriculum Under Kurikulum Merdeka - Asridayani Asridayani; Cantri Maesak; Rizal Nurzain; Fajriah Inayati (Journal of Innovation and Research in Primary Education, 2026)
This study examines the curriculum structure of Fiqh thaharah (ablution) instruction for Grade VII students in Madrasah Tsanawiyah (MTs) under Indonesia's Independent Curriculum (Kurikulum Merdeka). The research employed qualitative document analysis methodology, systematically examining official Learning Outcomes documents, approved textbooks, and teacher guidebooks for Phase D Fiqh instruction. Data were analyzed using manifest and latent content analysis frameworks, focusing on legal, cognitive, and spiritual dimensions of ablution pedagogy. Findings reveal that ablution instruction at MTs level represents a multidimensional pedagogical framework integrating three interconnected components: legal compliance through analytical engagement with jurisprudential postulates (istinbat al-ahkam), spiritual formation cultivating 'ubūdiyyah consciousness and noble character, and contemporary relevance through environmental fiqh addressing water conservation. The curriculum explicitly responds to students' dual developmental transition from mumayyiz to mukallaf status and from concrete to formal operational thinking, as theorized by Piaget. Unlike elementary instruction emphasizing procedural memorization, MTs curriculum prescribes innovative pedagogical strategies including Contextual Teaching and Learning (CTL) and Technological Pedagogical Content Knowledge (TPACK) integration. This research contributes a comprehensive theoretical framework demonstrating how classical Islamic jurisprudence can be pedagogically reconceptualized to address contemporary educational objectives while maintaining traditional integrity, offering evidence-based guidance for transformative fiqh education that cultivates critical reasoning and spiritual awareness.